Grazing decreased water use efficiency in Central Asia from 1979 to 2011 - Han, Qifei; Li, Chaofan; Zhao, Chengyi; Zhang, Yaoqi; Li, Shoubo (Ecological modelling, 2018)
•A significant evapotranspiration (ET) decreasing trend of 1.47–2.72 mm m−2 yr−1 during 1979-2011 was experienced throughout Central Asia.•Water use efficiency (WUE) exhibited increasing trends at a rate of 0.004 g C kg−1 H2O yr−1.•Grazing lowered ET and WUE by 7.47% and 3.60%, respectively, in Central Asia from 1979 to 2011.•Grazing intensity in Central Asia should be controlled to 0.17–0.39 head/ha, to achieve the maximum utilization of water efficiency. Accurate predictions of water vapor at large temporal and spatial scales are particularly important in global studies. In recent years, Central Asian grasslands have been subject to both intensive grazing and variability in climatic conditions. However, uncertainties about grazing on water cycling under climate change still exist. Therefore, the Biome-BGC grazing model was applied to assess the effects of grazing on evapotranspiration (ET) and water use efficiency (WUE). Three grassland types were studied during the period 1979–2011: forest meadow (FM), temperate grassland (TG) and desert grassland (DG). ET shows a gradual decreasing trend from FM (365.65 ± 36.86 mm m−2 yr−1) to DG (183.32 ± 21.15 mm m−2 yr−1), and WUE ranging from 0.62 ± 0.03 g C kg-1 H2O in FM to 1.12 ± 0.10 g C kg−1 H2O in TG, with an average of 0.83 ± 0.05 g C kg−1 H2O. Although there was a significant decrease in ET of 1.47–2.72 mm m−2 yr−1, WUE increased at a rate of 0.004 g C kg−1 H2O yr−1 in Central Asia. From 1979 to 2011, grazing lowered ET by 7.47% in Central Asia; the reduction rates for FM, TG and DG were 3.10%, 12.70% and 7.42%, respectively. In general, grazing decreased WUE by 3.60%. From non-grazed to grazed scenario, WUE increased by 6.86% for FM, but WUE decreased by 7.27% and 5.61% for TG and DG. An over-compensation of GPP under grazing might account for the higher WUE under certain grazing intensities. In order to achieve maximum utilization of water efficiency, proper grazing intensity for TG, DG and FM should be limited to 0.17, 0.39 and 0.38 head/ha, respectively.